Calculus of variations on time scales with nabla derivatives - Martins, N.
We prove a necessary optimality condition of the Euler-Lagrange type for variational problems on time scales involving nabla derivatives of higher order. The proof is done using a new and more general fundamental lemma of the calculus of variations on time scales. © 2008 Elsevier Ltd. All rights reserved.